Baseline Prevalence and Emergence of Protease Inhibitor Resistance Mutations following Treatment in Chronic HCV Genotype-1-Infected Individuals. Issue 8 (November 2015) - Nguyen, Linh Thuy; Gray, Emma; Dean, Jonathan; Carr, Michael; Connell, Jeff; Gascun, Cillian De; Nguyen, Lan Anh; O'Leary, Aisling; Bergin, Colm; Hall, William; Norris, Suzanne
Background: The HCV NS3/4A serine protease inhibitors (PIs) boceprevir (BOC), telaprevir (TVR) and simeprevir (SMV) are approved for treatment of chronic hepatitis C infection in combination with pegylated interferon and ribavirin. The present study investigated the prevalence of HCV NS3 drug resistance mutations (DRMs) associated with HCV genotype-1-infected individuals at baseline and in viral breakthrough following BOC and TVR treatment. Methods: HCV genotype-1-infected individuals were enrolled in a multicentre, prospective outcomes study. The HCV NS3 viral protease was analysed for DRMs at baseline ( n =164) and at viral breakthrough ( n =18) following BOC/ TVR treatment. Results: Viral NS3 protease subtype analysis showed 65.2% (107/164) were HCV subtype-1a and 34.8% (57/164) were HCV subtype-1b infections. Naturally occurring PI DRMs in NS3 (V36L, T54S, V55A, Q80K/R and I132V) were identified in 57.3% (94/164) cases at baseline. The NS3 Q80K polymorphism was found in 43/107 (40.2%) of HCV subtype-1a and exclusively in clade 1 (43/82; 52.4%) versus clade 2 viruses (0/25; 0%, P <10 -6 ). The pretreatment I132V variant was found in 78.9% (45/57) of subtype-1b. Of 18 patients who had viral breakthrough, the majority was subtype-1a (77.8%, 14/18). BOC/TVR-associated DRMs were detected in 94.4% (17/18), of which 64.7% (11/17) emerged on-treatment. Conclusions: To ensure the most appropriate direct-acting antiviral-based treatment regimen is employed, baseline reporting of clade and resistance mutations for HCV sub-type-1a using nucleotide sequence-based analysis is warranted prior to commencement of therapy.